ENHANCING STUDENTS’ PROBLEM-SOLVING SKILLS IN OSCILLATION AND SOUND WAVE CONCEPT BY UTILIZING A MULTIMEDIA BASED INTEGRATED INSTRUCTION - Siahaan, Parsaoran; Hidayat, Syarif Rokhmat; Kaniawati, Ida; Chandra, Didi Teguh; Samsudin, Achmad; Suhendi, Endi (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2018)
Problem-solving skill is one of the fundamental skills that must be mastered by students in the 21st century. This study identifies the enhancement of students’ problem-solving skill in oscillation and sound wave concept by utilizing multimedia based integrated instruction (MBI2). The subjects of this research were 30 junior high school students in Bandung-West Java. Data and analysis result showed that students’ problem-solving skill was enhanced in moderate criteria, showed by Ngain value of 0.57. Therefore, it can be concluded that MBI2 can enhance students’ problem-solving skills in oscillation and sound wave concept.